Trade shocks and social mobility: The intergenerational effect of import competition in Brazil - Andrés César; Matías Ciaschi; Guillermo Falcone; Guido Neidhöfer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
This paper investigates whether the impact of trade shocks on employment and wages persists across generations. Using survey data with retrospective information on parental employment, we study the causal effect of increased Chinese import competition in Brazilian industries on individuals with differently exposed fathers. Results show that several years after the shock, children of more exposed fathers have lower education and earnings, lower chances of formal jobs, and are more likely to rely on social assistance. These effects are substantially stronger for children from disadvantaged background, indicating that the shock had a negative impact on intergenerational mobility.
Keywords: I24; J62; F14; F16; J23; 330; Import competition; Education; Social Mobility; Incomes; Brazil